The Effects of Spatial Endogenous Pre-cueing across Eccentricities - Feng, Jing; Spence, Ian (Frontiers in Psychology, 2017)
Frequently, we use expectations about likely locations of a target to guide the allocation of our attention. Despite the importance of this attentional process in everyday tasks, examination of pre-cueing effects on attention, particularly endogenous pre-cueing effects, has been relatively little explored outside an eccentricity of 20o. Given the visual field has functional subdivisions that attentional processes can differ significantly among the foveal, perifoveal, and more peripheral areas, how endogenous pre-cues that carry spatial information of targets influence our allocation of attention across a large visual field (especially in the more peripheral areas) remains unclear. We present two experiments examining how the expectation of the location of the target shapes the distribution of attention across eccentricities in the visual field. We measured participants’ ability to pick out a target among distractors in the visual field after the presentation of a highly valid cue indicating the size of the area in which the target was likely to occur, or the likely direction of the target (left or right side of the display). Our first experiment showed that participants showed higher target detection rate and faster response of targets, particularly at eccentricities of 20o and 30o. There was also a marginal advantage of pre-cueing effects when trials of the same size cue were blocked compare to all trials mixed and randomized. Experiment 2 demonstrated higher target detection rate when the target occurred at the cued direction. This pre-cueing effect was greater at larger eccentricities and with a longer cue-target interval. Our findings on the endogenous pre-cueing effect across a large visual area were summarized using a simple model to assist in conceptualizing the modifications of the distribution of attention over the visual field. We also discuss our finding in light of cognitive penetration of perception, and highlight the importance of examining attentional process across a large field of view.